DESIGNING WHATSAPP BROADCAST USING VBA EXCEL AND JS NODES FOR MARKETING STRATEGY IN THE DIAN COLLECTION STORE - Moh.Imam Ma'ruf; Tholib Hariono (NEWTON: Networking and Information Technology, 2025)
This research aims to develop an automated WhatsApp Broadcast system for enhancing marketing efficiency in small retail businesses. The system was designed using Microsoft Excel as the user interface and Node.js as the backend for processing message delivery through WhatsApp Web. Excel is used to input customer data and promotional content, while Node.js enables the system to automatically read and send messages without manual intervention. The development process follows the waterfall model, which includes analysis, design, implementation, testing, and deployment. Testing was conducted using black-box testing to ensure the functionality of each component. The implementation at Dian Collection, a small shoe and sandal retail business, demonstrated that the system could successfully deliver messages to over 100 customers with a 95% success rate. The solution helps reduce human error, saves time, and provides message consistency in marketing communication. In addition, the use of familiar tools makes it easy to operate by non-technical users, especially in small and medium enterprises. This system presents a practical and low-cost alternative for businesses to adopt digital marketing strategies without relying on expensive third-party platforms. It also creates an opportunity for small businesses to transform their promotional activities into more structured, automated, and customer-oriented approaches.